2019
DOI: 10.1155/2019/1304152
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Mechanism of Acupuncture Analgesia on Visceral Pain: A Systematic Review

Abstract: Background/Aims. Despite the wide use of acupuncture for the management of visceral pain and the growing interest in the pathophysiology of visceral pain, there is no conclusive elucidation of the mechanisms behind the effects of acupuncture on visceral pain. This systematic review aims to provide an integrative understanding of the treatment mechanism of acupuncture for visceral pain. Methods. Electronic and hand searches were conducted to identify studies that involved visceral pain and acupuncture. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 67 publications
1
40
0
1
Order By: Relevance
“…Acupuncture was reported to inhibit visceral nociceptors/afferent fiber sensation, inflammatory cytokine release, and CNS activation by regulating the levels of endogenous opioids, serotonin, and NE, and so on. (26).The autonomic mechanism was found to play a role in the ameliorating effect of EA on gastric hypersensitivity in the present study. Alternations of the sympathetic nervous system and the hypothalamic-pituitary-adrenal (HPA) axis have been implicated in the development of visceral hypersensitivity in patients with FGID (27).…”
Section: Discussionsupporting
confidence: 60%
“…Acupuncture was reported to inhibit visceral nociceptors/afferent fiber sensation, inflammatory cytokine release, and CNS activation by regulating the levels of endogenous opioids, serotonin, and NE, and so on. (26).The autonomic mechanism was found to play a role in the ameliorating effect of EA on gastric hypersensitivity in the present study. Alternations of the sympathetic nervous system and the hypothalamic-pituitary-adrenal (HPA) axis have been implicated in the development of visceral hypersensitivity in patients with FGID (27).…”
Section: Discussionsupporting
confidence: 60%
“…Among distal acupoints, low back pain was the indication for BL40 in the lower limb, while insomnia was the indication for acupoint HT7 in the wrist ( Figure 5 ). Classification of acupoint indications into regional and distal types is consistent with the approach used in previous studies, where both regional and distal acupoints were mainly used for pain management during acupuncture, based on data mining from clinical trials [ 1 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 72%
“…The associations between symptom differentiations and acupuncture prescriptions are relatively clear in classical textbooks, although the associations from these classical textbooks are not likely to be prominent in clinical practice [ 9 , 10 ]. Previous studies have identified selections of acupoints for various diseases such as lumbar disc herniation, dysmenorrhea, rheumatoid arthritis, and visceral pain [ 11 , 12 , 13 , 14 ]. However, these findings do not directly reveal the specificity of acupoint indication; they only indicate which acupoints can be selected specifically for a particular disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, acupuncture and Chinese herbal medicines are recommended for cancer pain and serve to reduce opioid abuse. [27][28][29][30][31][32][33] TCM can also improve digestive symptoms, such as nausea, caused by radiotherapy and chemotherapy. [34][35][36] Moreover, psychiatric symptoms, such as anxiety and depression, in methamphetamine addicts during abstinence can be improved with electroacupuncture, 37 whereas depression-related insomnia and insomnia in cancer survivors can be treated with acupuncture, herbal medicines, and/or t'ai chi.…”
Section: Suggestionsmentioning
confidence: 99%